Efficacy of Clomiphene Citrate Alone Versus Clomiphene Citrate Plus Metformin in Anovulatory Infertility in Polycystic Ovarian Syndrome - Tanzila Rafiq, Naheed Hayat, Sadia Zainab, Sumaira Maqsood, Naheed Fatima, Piya Muhammad Musammat Rafi, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the efficacy of clomiphene citrate and clomiphene citrate with metformin in anovulatory infertility with PCOS (polycystic ovarian syndrome (PCOS). Study Design: Randomized controlled trial. Place and Duration of Study: This research took place in the Department of Gynecology and Obstetrics at the combined military hospital Bahawalpur. The study was carried out over a six-month period, starting on 1st November 2022 and concluding on 30 April 2023 Materials and Methods: The study comprised 176 married women aged between 18 and 40 years who had been experiencing anovulatory infertility and PCOS for more than 6 months. In group A, for a period of three menstrual cycles, patients received 500 mg of metformin three times a day consistently and 100 mg of clomiphene citrate daily from the fifth to the ninth day of their menstrual cycle. In contrast, patients in group B were given 100 mg of clomiphene citrate daily from the fifth to the ninth day of their menstrual cycle for up to three months. We recorded and analyzed the treatment efficacy for all participants in both groups. Results: In this study, the metformin and clomiphene combination showed a 71.59% ovulation rate compared to clomiphene alone (39.77 %). The pregnancy rate was 31.82% with clomiphene citrate (CC) and 64.77% with a combination (clomiphene citrate and metformin). Efficacy in the study was observed in 57 (64.77%) patients treated with metformin and CC. group and 28 (31.82%) patients in the clomiphene citrate alone group (p = 0.002). Conclusion: The findings from this study suggest that the combination of clomiphene citrate and metformin demonstrated superior efficacy compared to the use of clomiphene citrate alone in treating anovulatory infertility associated with polycystic ovary syndrome. Keywords: Polycystic ovarian syndrome, clomiphene citrate, metformin.